A paisagem cultural do Sítio Arqueológico Piracanjuba, Piraju, SP - Daves, Larissa Figueiredo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study aims to present the studies of painted ceramics in the area of three black stains Piracanjuba Archaeological Site, located in the city of Piraju, SP, on the Paranapanema River Valley region, São Paulo side. It is a litho-ceramic site associated with Tradition Tupiguarani . procedures for the production of painted ceramics were investigated in order to understand the possible operational chains of ceramic production, focusing on the answers that geography can give accordingly. The results were published in academic events and the community, in order to improve the analysis of archaeological material on display

Este trabalho tem por objetivo apresentar os estudos dos materiais cerâmicos pintados da área de três manchas pretas do Sítio Arqueológico Piracanjuba, localizado no Município de Piraju, SP, na região do Vale do Rio Paranapanema, lado paulista. Trata-se de um sítio lito-cerâmico associado à Tradição Tupiguarani. Foram investigados os procedimentos de produção da cerâmica pintada, com o intuito de compreender as possíveis cadeias operatórias de produção cerâmica, com enfoque para as respostas que a Geografia pode dar nesse sentido. Os resultados obtidos foram divulgados em eventos acadêmicos e para a comunidade, com a finalidade de aprimorar a análise do material arqueológico em tela
Keywords: Geografia; Arqueologia; Cerâmica; Indios Guarani; Indios Tupi; Geography; Sitios historicos - Piraju (SP); Sitios historicos - Piracanjuba (GO) -